A novel immunoinformatic approach for design and evaluation of heptavalent multiepitope foot-and-mouth disease virus vaccine - Mostafa R. Zaher; Mohamed H. El-Husseiny; Naglaa M. Hagag; Azza M. El-Amir; Mohamed E. El Zowalaty; Reham H. Tammam (BMC Veterinary Research)
Abstract Background Foot-and-mouth disease virus (FMDV) vaccine development can be a laborious task due to the existence of various serotypes and lineages and its quasi-species nature. Immunoinformatics provide effective and promising avenue for the development of multiepitope vaccines against such complex pathogens. In this study, we developed an immunoinformatic pipeline to design a heptavalent multi-epitope vaccine targeting circulating FMDV isolates in Egypt. Result B and T-cell epitopes were predicted and selected epitopes were proved to be non-allergenic, non-toxic, with high antigenicity, and able to induce interferon-gamma response. The epitopes were used to construct a vaccine by adding suitable linkers and adjuvant. Prediction, refinement, and validation of the final construct proved its stability and solubility, having a theoretical isoelectric point (PI) of 9.4 and a molecular weight of 75.49 kDa. The final construct was evaluated for its interaction with bovine toll-like receptor (TLR) 2 and 4 using molecular docking analysis and molecular dynamic simulation showed high binding affinity, especially toward TLR4. MM/GBSA energy calculation supported these findings, confirming favorable energetics of the interaction. Finally, the DNA sequence of the vaccine was cloned in pET-30a (+) for efficient expression in Escherichia coli. Conclusion The inclusion of computational and immunoinformatic approaches will ensure cost-effectiveness and rapid design of FMDV vaccine, decrease wet lab experimentation, and aid the selection of novel FMDV vaccines. While the vaccine demonstrates promising in-silico results, experimental assessment of vaccine efficiency is required.